Solanum torvum for Hypertension: a Systematic Review - Azlini Ismail*; Tuan Ashraf Faiz Tuan Anuar (Iranian Society of Pharmacognosy, 2023)
Solanum torvum is one of the plants mentioned in "Kitab Al-Tibb Pontianak", a historical medical manuscript which encompasses many traditional healings of Malay people for various ailments including of hypertension. This systematic review involves searching within Science Direct, SCOPUS, and PUBMED databases with the aim to find scientific evidences purporting this traditional claim. The keywords such as anti-hypertensive, angiotensin-converting enzyme (ACE) inhibitor, blood pressure, diuretic, vasodilation, Solanum torvum, and S. torvum were used with suitable Boolean operators. Sixteen research articles were finally included in this systematic review after considering some inclusions and exclusions criteria. The evidence that supported S. torvum use for hypertension included its capability in reducing blood pressure in normal and high fructose-induced hypertensive rats, and also its diuretic effect by increasing sodium excretion and total urinary output in normal and in nitric-oxide deprived rats, as well as the ability to inhibit ACE, the key enzyme that mediates consequential increment of blood pressure. On contrary, S. torvum also induced partial vasoconstriction and amplified the hypertensive effect in the nitric-oxide-deprived hypertensive rats. In conclusion, this review found scientific evidence asserting the traditional use of S. torvum for hypertension with some conflicting findings in some study models. Therefore, this ethnomedicinal claim warrants more scientific verification, especially on its effect on the essential hypertension model which is very common in humans but has not yet been explored.